Number lines in learning mathematic integer at the upper level - Mutia Amini; Fachri Helmanto; Arif Hidayat (Mitra Palupi, 2020)
Background: Students who have a good understanding of mathematics tend to have proud learning achievements. Good mathematics learning outcomes are influenced by intelligence and material mastery. However, teachers interact more with the white board than with students. students feel less enthusiastic because the teacher asks students to listen during the delivery of the lecture. Purpose: This study aims to determine the appropriate method in conveying integer material to elementary school students. Design and methods: This research uses classroom action research methods on 25 of fifth grade students of SD Negeri Cibunian in the second semester. This classroom action research adapted the cycle scheme proposed by Kemmis and Taggart. This scheme consists of a series of plots, including planning, acting, observing, reflecting, and revised plans for each cycle. Results: The results of this study reveal the use of number lines in mathematics subject matter integers in class V can improve student learning outcomes. This is evidenced by the percentage of students who score above the pre-cycle passing score of 28% or 7 students complete learning, in the first cycle it increases to 56% or 14 students complete their learning, and in the second cycle it reaches 80% or 20 students complete learning.